The Show must go on: How Students’ Perception on Online Learning in Bojonegoro - Iin Widya Lestari; Muhammad Fatoni (EDUVELOP, 2022)
Pandemic covid 19 spreads rapidly. Due to its quick breaks, a lot of countries decided to change some daily routine activies. One of affected aspects is education. Face to face learning has to be turned out into online learning in any level of schools. This present reseach aims to investigate and survey the students’ perception on online learning and what online fatlform mostly used by the students. This research is classified as qualitative research. This research took 74 participants. The data was obtained by distributing questionnaire which consist of some aspects namely method in delivering material, accessibility, beneft and challenges in onine learning and the most common used flatform during online learning. The result reveals that students prefer to get explanation in online learning. Internet connection and accessibility are complicated problems foun during online learning. Most of students also have lack of proper devices. They mostly use their smartphone with less memory devices. As a result, they have problems during online learning. In short, online learning is challenging for students. Microsoft teams is the most common online flatform used by the students in online learning